The Relationship of Stress Level to Stress Level And Menstrual Cycle Among Military Medical Cadets - Salsabila Azka; Trevicko Ardiansyah; Syahnadira Handadari; Adinda Suwarno; Mozart; Arief Setyawan; Rachma Hidana; Elies Fitriani (Perkumpulan Kedokteran Militer, 2025)
Background: Menstrual cycle regularity is an important indicator of reproductive health. Stress may disrupt menstrual function through neuroendocrine pathways, and military medical cadets may be vulnerable to both academic demands and semi-military training. This study aimed to determine the relationship between stress level and menstrual cycle among female military medical cadets at the Republic of Indonesia Defense University. Methods: This analytical observational study used a cross-sectional design. Ninety-five female medical cadets were recruited, and 92 respondents met the inclusion and exclusion criteria. Data were collected using Google Forms with the Perceived Stress Scale and a menstrual cycle questionnaire. The association between stress level and menstrual cycle was analyzed using the Chi-Square test, with statistical significance set at p < 0.05. Results: Most respondents experienced moderate stress (61/92; 66.3%), while 31 respondents (33.7%) had mild stress. Normal menstrual cycles were reported by 71 respondents (77.2%), whereas 21 respondents (22.8%) had abnormal menstrual cycles. The Chi-Square test showed a significant association between stress level and menstrual cycle (p = 0.008). Conclusion: Stress level was significantly associated with menstrual cycle patterns among military medical cadets. These findings highlight the importance of stress management and reproductive health monitoring in military medical education settings.